2023
DOI: 10.3390/f14122442
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Evolution and Prediction of Ecosystem Carbon Storage in the Yiluo River Basin Based on the PLUS-InVEST Model

Lei Li,
Guangxing Ji,
Qingsong Li
et al.

Abstract: Land-use change has a great impact on regional ecosystem balance and carbon storage, so it is of great significance to study future land-use types and carbon storage in a region to optimize the regional land-use structure. Based on the existing land-use data and the different scenarios of the shared socioeconomic pathway and the representative concentration pathway (SSP-RCP) provided by CMIP6, this study used the PLUS model to predict future land use and the InVEST model to predict the carbon storage in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…They found that the associated model could effectively assess the impact of future urban expansion on the environment (He et al 2016). The studies, as mentioned earlier, have achieved satisfactory results by coupling changes in land use with the InVEST model, which enables a clear reflection of the spatial distribution pattern of carbon storage (Adelisardou et al 2022;Li et al 2023).…”
Section: Introductionmentioning
confidence: 90%
“…They found that the associated model could effectively assess the impact of future urban expansion on the environment (He et al 2016). The studies, as mentioned earlier, have achieved satisfactory results by coupling changes in land use with the InVEST model, which enables a clear reflection of the spatial distribution pattern of carbon storage (Adelisardou et al 2022;Li et al 2023).…”
Section: Introductionmentioning
confidence: 90%